The impact of land use and cover change on above and below-ground carbon stocks of the miombo woodlands since the 1950s: a systematic review protocol - Syampungani, S.; Clendenning, J.; Gumbo, D.J.; Nasi, Robert; Moombe, K.B; Chirwa, P.; Ribeiro, N; Grundy, I.; Matakala, N; Martius, C.; Kaliwile, M; Kabwe, G; et al. (Springer, 2014)
Increasingly, forests are on the international climate change agenda as land use and cover changes drive forest and carbon loss. The ability of forests to store carbon has created programs such as Reducing Emissions from Deforestation and Degradation plus (REDD+), in order to provide incentives for particular land uses and forest management practices. A critical element to REDD+ is the ability to know the carbon-storage potential of an ecosystem, and the factors likely to affect the rate of carbon accumulation or the maximum amount stored. Most REDD+ initiatives have focused on humid tropical forests because of their large stocks per unit area. Less attention has been paid to the carbon-storage potential of tropical dry forests, woodlands and savannas. Although these ecosystems support a lower biomass per unit area, they are more widespread than humid forests. This proposed systematic review examines miombo woodlands, which are the most extensive vegetation formation in Africa and support over 100 million people. We ask: To what extent have changes in land use and land cover influenced above- and below-ground carbon stocks of miombo woodlands since the 1950s?We will search systematically for studies that document the influence of land use and cover change on above and below ground carbon in miombo woodlands since the 1950s. We will consult bibliographic databases and an extensive grey literature network, including government reports and forestry offices. Relevant studies will examine the impacts of human activities, fire and other land use or cover changes that affect wood biomass or soil carbon in the miombo region. All included studies will be assessed for the soundness and scientific validity of their study design. A quantitative synthesis will tabulate estimates of various parameters necessary to assess carbon stocks and changes across climate and geological factors; and a qualitative analysis will describe the governing land and forest policies. Understanding the impact that land uses and the associated changes have on carbon storage in the miombo woodlands will contribute to more informed forest management policies and better guided strategies for the United Nations Framework Convention on Climate Change.